TINJAUAN GAYA KEPEMIMPINAN PADA PERUSAHAAN PT VICTORY INTERNASIONAL FUTURES - Shofiana Syam (Cross-border, 2021)
This study aims to figure out the general manager's leadership style at PT. Victory International Futures. The type of research used is descriptive qualitative. The writing of this final project is the result of research conducted for approximately 2 (tow) months from May to July. From the result of the study it can be concluded that the general manager at PT Victory Internasional Futures is still not good, it is proven that many employees resign on the grounds of not being able to find coustomers and not achieving the predetermined targets.